MicroRNAs and their target gene networks in renal cell carcinoma - Redova, Martina; Svoboda, Marek; Slaby, Ondrej (Biochemical and biophysical research communications, 2011)
MicroRNAs (miRNAs) are non-protein-coding short single stranded RNAs in the size range 19-25 nucleotides that are associated with gene regulation at the transcriptional and translational level. Recent studies have proved that miRNAs play important roles in a large number of biological processes, including cellular differentiation, proliferation, apoptosis, etc. Changes in their expression were found in a variety of human cancers, including renal cell carcinoma pathogenesis. Specific miRNA alterations were associated with key pathogenetic mechanisms of renal cell carcinoma like hypoxia or epithelial-mesenchymal transition. In this review, we summarize the current knowledge of miRNA functions in renal cell carcinoma with an emphasis on miRNAs potential to serve as a powerful biomarker of disease and a novel therapeutic target in oncology.
Keywords: nádory ledvin; regulace genové exprese u nádorů; Humans; MicroRNAs; hypoxie buňky; genové regulační sítě; Neoplasm Invasiveness; Gene Regulatory Networks; lidé; proliferace buněk; apoptóza; Neoplasm Metastasis; metastázy nádorů; Cell Proliferation; karcinom z renálních buněk; Carcinoma, Renal Cell; mikro RNA; invazivní růst nádoru; Gene Expression Regulation, Neoplastic; Cell Hypoxia; Kidney Neoplasms; Apoptosis